Implementasi Model Pembelajaran Sentra Bermain Peran Dalam Stimulasi Rasa Percaya Diri Anak KB 4 di PAUD Terpadu Al-Furqan Jember - Karinafisatuzahro (Fakultas Keguruan dan Ilmu Pendidikan, 2026)
This study was motivated by the importance of implementing role play center learning as a strategy to stimulate self-confidence in early childhood. The study examined the implementation of the role play center learning model in stimulating the self-confidence of KB 4 children at PAUD Terpadu Al-Furqan Jember. The purpose of this study was to describe the planning, implementation, and evaluation of role play center learning related to the stimulation of children's self-confidence. This study employed a descriptive qualitative approach. Data were collected through observation, semi-structured interviews, and documentation involving the role play center teacher, the head of the curriculum division, and the principal. The data were analyzed through the stages of data collection, data reduction, data presentation, and conclusion drawing, while data trustworthiness was ensured through source triangulation and technique triangulation. The findings showed that the implementation of role play center learning was carried out systematically through the stages of planning, implementation, and evaluation. During the implementation stage, the teacher provided structured scaffolding through environmental setup, pre-play, during-play, and post-play activities. The stimulation of children's self-confidence occurred indirectly, primarily through teacher guidance that encouraged children to speak, answer questions, express their opinions, and perform in front of others. However, this stimulation tended to occur only through communication with the teacher using prompting questions. During the evaluation stage, the teacher documented the children's learning process through observation, checklists, anecdotal records, documentation, and reflection with fellow teachers, but did not specifically evaluate the four indicators of self-confidence.
:: Finalisasi file repositori 21 Juli 2026_Kurnadi
Keywords: early childhood education; learning implementation; role play center learning; self-confidence.